A new dimethoxy dihydrochalcone isolated from the shoots of Empetrum nigrum L. Issue 20 (13th October 2022) - Ponkratova, Anastasiia O.; Whaley, Andrei K.; Orlova, Anastasia A.; Smirnov, Sergey N.; Serebryakov, Evgeny B.; Proksch, Peter; Luzhanin, Vladimir G.
Abstract: A new dihydrochalcone, 2', 4'-dimethoxydihydrochalcone (1 ), together with 7 known compounds, 2', 4'-dihydroxydihydrochalcone (2 ), 2'-hydroxy-4'-methoxydihydrochalcone (3 ), 2'-hydroxy-4'-methoxychalcone (4 ), 1-(3, 5-dihydroxy-4-methoxyphenyl)-2-(3-hydroxyphenyl) ethane (5 ), 2, 3, 4, 7-tetramethoxy-9, 10-dihydrophenanthrene (6 ), 5-hydroxy-2, 3, 4-trimethoxy-9, 10-dihydrophenanthrene (7 ) and 5, 7-dihydroxy-6, 8-dimethyl flavanone (8 ) were isolated from the shoots of Empetrum nigrum L. The structures of these compounds were elucidated using 1D and 2D NMR experiments along with HR-ESI-MS. Compound 6 is reported for the genus Empetrum for the first time.